Transverse propagation of ultraviolet and infrared femtosecond laser pulses in photonic crystal fibers - Baghdasaryan, Tigran; Geernaert, Thomas; Mergo, Pawel; Berghmans, Francis; Thienpont, Hugo (Photonics Letters of Poland, 2012)
We studied the influence of the angular orientation of a photonic crystal fiber (PCF) on the optical power that reaches the fiber core during femtosecond grating inscription at 267 nm and 800 nm. In our numerical study we considered two types of PCFs: three PCF designs with a standard hexagonal lattice and one highly birefringent PCF with three rows of air holes. A dedicated figure of merit, the Transverse Coupling Efficiency (TCE), is used throughout the paper to estimate the influence of the PCF cladding on the laser power that reaches the core region. We found that at an inscription laser wavelength of 800 nm and for a high filling factor hexagonal lattice PCF, the TCE can reach 1.4. This means that the microstructure can actually help delivering a higher power to the core region of the PCF than what can be achieved with a conventional step-index fiber with similar diameter. For the highly birefringent PCF even higher TCE values (up to 2.8) can be achieved for a wide range of orientations. Full Text: PDF References A. Othonos, K. Kalli, Fiber Bragg Gratings (Artech House 1999) W. Wadsworth, R. Percival, G. Bouwmans, J. Knight, J. and P. Russell,"High power air-clad photonic crystal fibre laser", Opt. Express 11, 48 (2003)[CrossRef] Nature Photonics, Optical-fibre Sensors, Tech. Focus 2, 158 (2008) D. N. Nikogosyan,"Multi-photon high-excitation-energy approach to fibre grating inscription", Meas. Sci. Tech. 18, R1 (2007)[CrossRef] M. Becker, J. Bergmann, S. Brückner, M. Franke, E. Lindner, M. W. Rothhardt and H. Bartelt,"Fiber Bragg grating inscription combining DUV sub-picosecond laser pulses and two-beam interferometry", Opt. Express 16, 19169 (2008)[CrossRef] S. J. Mihailov, D. Grobnic, H. Ding, C. W. Smelser and J. Broeng,"Femtosecond IR laser fabrication of Bragg gratings in photonic crystal fibers and tapers", IEEE Photon. Technol. Lett. 18, 1837 (2006)[CrossRef] T. Geernaert, K. Kalli, C. Koutsides, M. Komodromos, T. Nasilowski, W. Urbanczyk, et al.,"Point-by-point fiber Bragg grating inscription in free-standing step-index and photonic crystal fibers using near-IR femtosecond laser", Opt. Lett. 35, 1647 (2010)[CrossRef] T. Allsop, K. Kalli, K. Zhou, G. N. Smith, M. Komodromos, J. Petrovic, et al.,"Spectral characteristics and thermal evolution of long-period gratings in photonic crystal fibers fabricated with a near-IR radiation femtosecond laser using point-by-point inscription", J. Opt. Soc. Am. B 28, 2105 (2011)[CrossRef] G. D. Marshall, D. J. Kan, A. A. Asatryan, L. C. Botten, and M. J. Withford,"Transverse coupling to the core of a photonic crystal fiber: the photo-inscription of gratings", Opt. Express 15, 7876?7887 (2007)[CrossRef] S. Pissadakis, M. Livitziis, and G. Tsibidis,"INVESTIGATIONS ON THE BRAGG GRATING RECORDING IN ALL-SILICA, STANDARD AND MICROSTRUCTURED OPTICAL FIBERS USING 248 NM 5 PS, LASER RADIATION", J. Eur. Opt. Soc. Rapid Publ. 4, 09049 (2009)[CrossRef] T. Baghdasaryan, T. Geernaert, M. Becker, K. Schuster, H. Bartelt, M. Makara, et al.,"Influence of Fiber Orientation on Femtosecond Bragg Grating Inscription in Pure Silica Microstructured Optical Fibers", IEEE Phot. Tech. Lett. 23, 1832 (2011)[CrossRef] T. Baghdasaryan, T. Geernaert, F. Berghmans, and H. Thienpont,"Geometrical study of a hexagonal lattice photonic crystal fiber for efficient femtosecond laser grating inscription", Opt. Express, 19, 7705 (2011)[CrossRef] T. Geernaert, T. Nasilowski, K. Chah, M. Szpulak, J. Olszewski, G. Statkiewicz, et al.,"Fiber Bragg Gratings in Germanium-Doped Highly Birefringent Microstructured Optical Fibers", IEEE Phot. Tech. Lett. 20, 554 (2008)[CrossRef]